Socio-political conflicts in the Democratic Republic of Congo : an analysis from Paul Ricoeur's perspective - (:unkn) unknown (My University, 2023)
Summary:Socio-political conflicts and repeated crises that have bloodied the Democratic Republic of Congo for decades undermine the lives of its people and its future. A geostrategic country for Africa, and undoubtedly one of the richest in the world in natural resources but with a population kept in poverty. Indeed, poor governance weakens institutions, generates conflicts, provokes revolt and violence. The Congolese crisis comes from the loss of traditional, ethical and anthropological values. This justifies the lack of honesty, a sense of dignity and honor, internal and external cohesion between saying and doing it, the lack of justice and sincere dialogue and the corruption that is at the top of the anti-values that plague this country. To do this, we advocate for good governance as an effective means of preventing and managing social conflicts.In this sense, we need leaders who hold themselves internally, that is, tried men who have a morality and principles of life that testify to the political responsibility they have for the destiny of a nation and a people.Moreover, it should be noted that democracy is multifaceted. That being said, what democracy for Africa? It wisely appears that if Africa continues to imitate the political system, the disaster will be even greater.In the dynamics of this thought, the experience of African sapiential life leads us to appeal to practical wisdom in the management of the res publica for peaceful coexistence. That is why good governance based on the sapience we call : "sophiacracy" is an emergency for conflict prevention and management in the Democratic Republic of CongoBy Godefroid Nzila Yaav'
Keywords: African Research